An unusual case of tracheo-pleural fistula and cardiac metastases in oropharyngeal carcinoma: a case report and review of the literature. Issue 1 (December 2016) - Ferrari, Daris; Codecà, Carla; Viale, Giulia; Bocci, Barbara; Broggio, Francesca; Crepaldi, Francesca; Violati, Martina; Luciani, Andrea; Bauer, Dario; Moneghini, Laura; Bulfamante, Gaetano; Foa, Paolo
Abstract Background Oropharyngeal cancer is frequently associated with human papilloma virus, that also represents a strong prognostic factor. Local relaps and treatment-related complications are frequent, whereas distant metastases occur in about 25% of patients. Case presentation A 49 years-old male presented with a loco-regionally advanced oropharyngeal squamous cell carcinoma and was treated with concomitant chemoradiation. A complete clinical and pathological response was achieved, but the occurrence of necrotising tracheo-esophagitis, with tracheo-mediastino-pleural fistula formation, further complicated the subsequent clinical course. The patient died suddenly. Autopsy revealed multiple myocardial and epicardial metastases from oropharyngeal squamous cell carcinoma. Conclusions Even in case of a transient complete local response, the potential occurrence of severe complications and distant metastases, although infrequent, should be considered. Cardiac metastases are frequently underestimated, as they are often asymptomatic, but may lead to sudden death. Further efforts are needed to improve diagnosis and therapy in this setting.